A comparative Anatomical Study of Diplotaxis Spp. DC. (Brassicaceae ) Grown in Diyala Province - Iraq - Wadi, Khazal Dibba; Salman, Zeinab Nasrallah (Journal of agricultural, environmental and veterinary sciences, 2018)
The current study is a comparative anatomical study of Diplotaxis spp DC species of the Brassicaceae which are growing in Diyala province { Diplotaxis acris (Fossk.) Boiss. Diplotaxis erucoid (L.) DC, Diplotaxis harra (Forssk) Boiss}. The anatomical study included the dissection of the stems, the petioles and the leaf blade. The results of the present study showed that the anatomical characteristics have a great taxonomic significance, which helps in isolation and diagnosis, through the many variations shown by the anatomical characteristics of the studied species. The stem showed significant anatomical properties in terms of the shape of the cross section. D.rucoid was characterized as having ribbed stems and was characterized by the presence of collenchyma cells at the corners of the ribs to give support and attribution as well as flexibility in motion. D.harra also characterized epidermis cells as rectangular. The cortex also varied in the species of cells, the number of rows of chlorenchyma and paranchyma, and the number and distribution of vascular bundles, the number of arms of wood and the number of vessels in each arm. The variances included the cross section of the leafblade and the shape of the cross-section was important in isolation and diagnosis. It also varied in thickness, epidermis, vascular forms, numbers, distribution, cortex thickness and layers. The leaves were Monoficial in type D.harra It is also characterized by its lack of sponge cells while the two species of D. acris and D. erucoid were Bificial. The vertical sections of leaves, especially the mesophyll, varied widely, in the thickness of blade, dermis, epidermis ,forms of the central vascular bundles and the preparation of the arms and elements. All these qualities have contributed as an addition of distinctive qualities to each important species in its isolation and diagnosis.
Keywords: anatomical study; cruciferous family; biological classification